2020
DOI: 10.1186/s12906-020-03036-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Neuromodulation improved inflammation and sympathovagal ratio in patients with primary biliary ssscholangitis and inadequate response to Ursodeoxycholic acid: a pilot study

Abstract: Background: At present, ursodeoxycholic acid (UDCA) is internationally recognized as a therapeutic drug in clinic. However, about 40% Primary Biliary Cholangitis (PBC) patients are poor responders to UDCA. It has been demonstrated that Transcutaneous Neuromodulation (TN) can be involved in gut motility, metabolism of bile acids, immune inflammation, and autonomic nerve. Therefore, this study aimed to explore the effect of TN combined with UDCA on PBC and related mechanisms. Methods: According to inclusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Colitis causes gut dysbiosis, increase bacterial translocation to the liver leading to hepatic damage in mice with DSS, and is associated with an increase in the level of hepatic LPS ( Cheng et al, 2018 ; Svegliati-Baroni et al, 2020 ). The inflammatory factors secreted by liver can enter intestine, and aggravate the damage of intestinal lining and disrupt microbiota through the bile secretion into the intestinal lumen ( Yang et al, 2020 ). Several shreds of evidence that liver injury diseases are causally associated with impaired intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Colitis causes gut dysbiosis, increase bacterial translocation to the liver leading to hepatic damage in mice with DSS, and is associated with an increase in the level of hepatic LPS ( Cheng et al, 2018 ; Svegliati-Baroni et al, 2020 ). The inflammatory factors secreted by liver can enter intestine, and aggravate the damage of intestinal lining and disrupt microbiota through the bile secretion into the intestinal lumen ( Yang et al, 2020 ). Several shreds of evidence that liver injury diseases are causally associated with impaired intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of “Xingnao Kaiqiao Acupuncture” in traditional Chinese medicine [ 15 ], three acupuncture points were selected as the target points: bilateral Neiguan [ 16 ] (PC6, on the palmar side of the forearm, 3 cm proximal to the transverse carpal crease, between the palmaris longus tendon and the radial flexor carpi tendon), Yintang [ 17 ] (GV29 ], on the forehead of the human body, between the two eyebrows) and bilateral Zusanli [ 18 ] (ST36, 3 inches below the outer knee). Patients in the TEAS group received perioperative TEAS by two experienced researchers and the treatment time was 30 min before the induction of anesthesia until the end of the surgery, 1 day before operation, and from the first day to the third day after the operation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, therapeutic manipulation of the gut–brain axis has become of interest in this group of patients. Recently, it has been shown that neuromodulation via a tibial nerve acupuncture point increased parasympathetic drive and reduced Il6 and gamma-glutaminetransferase (GGT) levels in a small group of patients with PBC who previously had an inadequate response to ursodeoxycholic acid [8 ▪ ]. This pilot study holds promise for the manipulation of the gut–brain axis as a novel therapeutic strategy for this difficult to treat condition.…”
Section: Systemic Effects Of the Gut–brain Axis Via The Cholinergic A...mentioning
confidence: 99%